2008
DOI: 10.1037/0021-9010.93.4.831
|View full text |Cite
|
Sign up to set email alerts
|

Theories of job stress and the role of traditional values: A longitudinal study in China.

Abstract: This study examines how traditionality influences the relationships between job stressors and health. A sample of 496 Chinese employees provided longitudinal questionnaire data, and their health was assessed by collecting blood samples and monitoring blood pressure. The results indicated that the positive relationship between job control and health was stronger among the less traditional workers, whereas the positive relationship between distributive justice and health was stronger among the more traditional w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 92 publications
2
131
0
3
Order By: Relevance
“…In addition, as more and more organizations operate in a global environment, future research might extend our findings not only by using samples from other national cultures but also by exploring the Asia Pacific Business Review 243 role of cultural and individual differences within specific countries. With its rapid industrialization and the increased diversity in values (Xie, Schaubroeck, and Lam 2008), China, in particular, provides a rich ground for testing the extent to which contextual and individual difference variables may affect the emergence and functioning of ethical leadership.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, as more and more organizations operate in a global environment, future research might extend our findings not only by using samples from other national cultures but also by exploring the Asia Pacific Business Review 243 role of cultural and individual differences within specific countries. With its rapid industrialization and the increased diversity in values (Xie, Schaubroeck, and Lam 2008), China, in particular, provides a rich ground for testing the extent to which contextual and individual difference variables may affect the emergence and functioning of ethical leadership.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionality, defined as the acceptance of customs and norms of a traditional society (e.g. Confucian value system), may be an important factor in predisposing Chinese people toward individual attitudes and behaviors (Xie, Schaubroeck and Lam 2008). Recent empirical evidence also demonstrated that traditional Chinese values significantly impacted employees' organizational citizen behavior (OCB) (Yang 2003).…”
Section: Introductionmentioning
confidence: 98%
“…globalization) could diminish employee job control. Recent studies in China for example found that job task structures are designed by high ranking authorities, and employees are expected to follow instructions 17) . As organizations strive to achieve the global competition agenda we expect that employees will be confronted with reduced supervisory support.…”
mentioning
confidence: 99%